Compliance with anticonvulsant therapy in a hospital clinic and in the community. - Mucklow, J C (1978)
1 Seizure control, saliva anticonvulsant concentration, prescribing habits and compliance with anticonvulsant medication have been compared in 86 epileptic subjects attending either a specialist hospital clinic or general practice surgeries. 2 Of all subjects experiencing recurrent seizures 70% had saliva concentrations of phenytoin below the range equivalent to the 'therapeutic range' of plasma concentration. Mean saliva phenytoin concentrations did not differ significantly between the two treatment settings and were low largely because of the low mean dosage prescribed. 3 Eleven subjects in all had no detectable phenytoin in their and could clearly be identified as noncompliant. Freedom from seizures appeared to predispose to poor compliance in these subjects as well as among those admitting repeated omission of doses.